Intergenerational equity : environmental and cultural concerns - Cottier, Thomas; Lalani, Shaheeza; Siziba, Clarence (Brill Nijhoff, 2019)
In Intergenerational Equity: Environmental and Cultural Concerns, the editors have produced an important, broad-based volume on intergenerational equity. The authors explore the principle of intergenerational equity in many dimensions, from the theoretical to the practical. While the primary focus is on intergenerational equity in the context of environmental resources and cultural heritage, the principle is also addressed in a broad array of other contexts. The final section of the volume considers intergenerational justice as it applies to Indigenous peoples, genocide, migration, sovereign wealth funds and foreign investment. The chapters also provide a critical analysis of the issues and a consideration of the difficulties in implementing intergenerational equity.
"This book is a collection of legal, philosophical and historical papers selected for presentation at a Conference of 9 October 2015, which was hosted by the Rectors' Conference of the Swiss Universities (CRUS) joint doctoral programme between the Universities of Fribourg and Bern."
Keywords: Law -- Congresses.; Intergenerational relations -- Congresses.; Distributive justice -- Congresses.; Environmental law, International -- Congresses.; Sociological jurisprudence -- Congresses.; Droit -- Congrès.; Relations entre générations -- Congrès.; Justice distributive -- Congrès.; Sociologie juridique -- Congrès.; International environmental law.; LAW -- Essays.; LAW -- General Practice.; LAW -- Jurisprudence.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; LAW -- Reference.; Distributive justice; Environmental law, International; Intergenerational relations; Law; Sociological jurisprudence; Intergenerational equity.; Social justice.; Sustainable development.; Conference papers and proceedings